Efektifitas Program Kalimasada Kota Surabaya Di Kelurahan Semolowaru Sebagai Penerapan E-Government Di Indonesia - Putri Aleeah Antasah; Ghulam Maulana Ilman (Policy and Maritime Review, 2023)
E-government demonstrates the strategic and coordinated use of information and communication technology (political ICT) in public administration and decision-making. Since the enactment of Presidential Decree No. 3 of 2003 concerning Political Strategy for the development of e-government and government capabilities, it is necessary to take advantage of advances in information and communication technology. The development of e-government-based public services. at the national level, many local governments have initiatives to do this by implementing E-Government. The city of Surabaya, which is the largest city in Indonesia, has not escaped the influence of these times, the Surabaya city government has begun to launch digital-based programs from various fields, one of which is in the field of government, through the Surabaya City Population and Civil Registration Service, the government innovates a system digital-based services by utilizing application platforms and websites which are used as the main window between residents who apply for Population Administration services and the Surabaya City Population and Civil Registration Service. One of the programs that has become the output of this digital-based government is the Surabaya City KALIMASADA program which has been implemented in almost all urban villages in Surabaya City.